PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Suprayitno, Yuneth Tahapary, Marjam Desma Rahadhini & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the significance of the influence of transformational leadership and cultural organization against organization commitment, analyze the significance of the influence of organization commitment, transformational leadership and cultural organization against the employee performance, analyze commitment organization in mediate transformational leadership and cultural organization against the employee performance. Sample the population and in this research was all of the employees Secretariat DPRD Surakarta which consisted of 32 people. Data collection method uses a questionnaire. The practical data using analysis techniques, reliability test, classical test, and the hypothesis. Based on the results of the analysis it can be concluded that leadership commitment transformational significant impact on employees organization, culture organization has no significant impact on the commitment organization on employees, commitment organization not significant of the performance of employees, leadership transformational not significant of the performance of employees, culture organization significant of the performance employees, commitment organization not mediate influence leadership transformational of the performance employees, commitment organization mediate the influence of culture organization of the performance employees.Keywords: transformational leadership, cultural organization, organization commitment, employee performance